STRATEGI PEMASARAN MENGGUNAKAN SALES PROMOTION GIRLS (SPG) DALAM PERSPEKTIF EKONOMI ISLAM - Nurudin, Nurudin (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2018)
Sales promotion girl (SPG) is a profession that is engaged in the marketing or promotion of a product. This profession typically uses women who have interesting physical character as an attempt to attract the attention of consumers.SPG is required to have skills in offering goods/services of the company. Usually, the way product offering by SPG has some interesting characteristics in an attempt to attract the attention of consumers. With the promotion system using the services of a consumer not uncommon SPG gravitated towards these products but because of the physical appearance of the SPG looks sexy in that dress. This was done as an attempt to boost the product so well-known and was sold to the general public. This research is field research using the method of observation, interview, and documentation. This type of research is qualitative research that is data presented with words. By using a descriptive method. Islamic Economics perspective on marketing strategies using SPG is not allowed if the SPG sexy dress and exposes her body accentuating i.e., lest consumers buy goods, not because of the quality of its products.